1997
DOI: 10.2144/97224rr01
|View full text |Cite
|
Sign up to set email alerts
|

Recombinant HMG1 Protein Produced in Pichia pastoris : A Nonviral Gene Delivery Agent

Abstract: ABSTRACT

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
24
0

Year Published

1998
1998
2012
2012

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(25 citation statements)
references
References 24 publications
1
24
0
Order By: Relevance
“…Endogenous proteins such as members of the high mobility group proteins (HMG) and histones have also been used as pDNA delivery systems as such [166,167] or in combination with conventional lipids and polymers [168] to increase transfection efficiency [169]. These proteins were able to enhance pDNA nuclear translocation and transfection efficiency to some extent, most likely due to their innate DNA binding and condensing properties, as well as their intrinsic NLSs.…”
Section: Nonviral Chromatin Tethering Factorsmentioning
confidence: 99%
“…Endogenous proteins such as members of the high mobility group proteins (HMG) and histones have also been used as pDNA delivery systems as such [166,167] or in combination with conventional lipids and polymers [168] to increase transfection efficiency [169]. These proteins were able to enhance pDNA nuclear translocation and transfection efficiency to some extent, most likely due to their innate DNA binding and condensing properties, as well as their intrinsic NLSs.…”
Section: Nonviral Chromatin Tethering Factorsmentioning
confidence: 99%
“…Tissue-specific gene transfer could be achieved naturally and effectively through the cell specificity of virus receptors. 46 However, there is a risk of vector toxicity through viral infection of the host cells. Also, the limited size of transgenes often presents a serious obstacle.…”
Section: Il-4 Antagonistic Mutant Dna Inhibits Allergic Airway Inflammentioning
confidence: 99%
“…Also, attachment to cellular DNA binding proteins including histones 14 and high-mobility group (HMG) proteins 15 , as well as DNA containing the Simian Virus 40 (SV40) promoter and origin of replication 16 Interestingly, several groups have observed that the expression efficiencies of cationic lipid-, polymerand peptide-based transfection reagents were two-to several hundred-fold higher in dividing as compared to non-dividing cells , have been investigated. These attempts at improving the transport of DNA to the nucleus have however met with limited success.…”
mentioning
confidence: 99%